2010
DOI: 10.1007/s12562-010-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variations in age and size at settlement of 8 emperor fishes (Lethrinidae) at the southern Ryukyu Islands, Japan

Abstract: Molecular and otolith analyses were conducted for 173 settlement-stage larvae of emperor fishes (family Lethrinidae) collected by light traps at Ishigaki Island, southern Japan, in July and August (summer season), to (1) present diagnostic DNA markers for identification of lethrinid species and (2) compare the size and age at settlement of each species. PCR-RFLP and direct nucleotide sequencing analyses identified 8 species. Size (standard length, SL) at settlement differed significantly between species; Lethr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Many juveniles of these species feed mainly on small crustaceans until they reach a certain body size, at which their foraging abilities and nutrient requirements change (Nakamura et al 2003;Kamukuru and Mgaya 2004). The lethrinids and lutjanids utilize shallow seagrass/mangrove canopies as nurseries or feeding grounds in many Indo-Pacific regions (Unsworth et al 2008b(Unsworth et al , 2009Kimirei et al 2011;Nakamura et al 2010Nakamura et al , 2012Berkström et al 2013). We found their densities to increase at the intertidal stations during flood tides, especially at W. Previous researchers have found that some decapods move into shallow areas during flood tides, and some carnivorous fish may follow them at these times for foraging (Klumpp and Nichols 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Many juveniles of these species feed mainly on small crustaceans until they reach a certain body size, at which their foraging abilities and nutrient requirements change (Nakamura et al 2003;Kamukuru and Mgaya 2004). The lethrinids and lutjanids utilize shallow seagrass/mangrove canopies as nurseries or feeding grounds in many Indo-Pacific regions (Unsworth et al 2008b(Unsworth et al , 2009Kimirei et al 2011;Nakamura et al 2010Nakamura et al , 2012Berkström et al 2013). We found their densities to increase at the intertidal stations during flood tides, especially at W. Previous researchers have found that some decapods move into shallow areas during flood tides, and some carnivorous fish may follow them at these times for foraging (Klumpp and Nichols 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to approximate early growth trajectories, VBGF models were constrained to an established or inferred (from similar taxa) length at settlement (i.e., FL at age 0). For L. xanthochilus , this was 3.0 cm ( Nakamura et al, 2010 ); for L. gibbus and L. rufolineatus , this was 3.5 cm ( Mori, 1984 ; Nanami & Yamada, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Identifications were conducted to the lowest possible taxonomic category (Nakabo, 2002), and standard length ( L s ) was measured to the nearest 0·1 mm. Because settlement‐stage lethrinid larvae do not possess species‐specific colour patterns, their species were identified using molecular analysis described in Nakamura et al (2010). Thirty‐five species from seven families (Apogonidae, Pomacentridae, Chaetodontidae, Lethrinidae, Lutjanidae, Mullidae and Acanthuridae), which are generally distributed near the Ryukyu Islands (Nakamura & Sano, 2004; Shibuno et al , 2008), were selected based on their egg types ( i.e.…”
Section: Methodsmentioning
confidence: 99%